Platinum Oxide Nanoparticles for Electrochemical Hydrogen Evolution: Influence of Platinum Valence State. Issue 18 (10th December 2019) - Nichols, Forrest; Lu, Jia En; Mercado, Rene; Dudschus, Ryan; Bridges, Frank; Chen, Shaowei
Abstract: Electrochemical hydrogen generation is a rising prospect for future renewable energy storage and conversion. Platinum remains a leading choice of catalyst, but because of its high cost and low natural abundance, it is critical to optimize its use. In the present study, platinum oxide nanoparticles of approximately 2 nm in diameter are deposited on carbon nitride (C3N4) nanosheets by thermal refluxing of C3N4 and PtCl2 or PtCl4 in water. These nanoparticles exhibit apparent electrocatalytic activity toward the hydrogen evolution reaction (HER) in acid. Interestingly, the HER activity increases with increasing Pt 4+ concentration in the nanoparticles, and the optimized catalyst even outperforms commercial Pt/C, exhibiting an overpotential of only −7.7 mV to reach the current density of 10 mA cm −2 and a Tafel slope of −26.3 mV dec −1 . The results from this study suggest that the future design of platinum oxide catalysts should strive to maximize the Pt 4+ sites and minimize the formation of the less active Pt 2+ species. Abstract : Valence importance : Platinum oxide nanoparticles deposited on carbon nitride nanosheets outperform Pt/C toward the hydrogen evolution reaction in acid. The Pt IV species was found to be far more active than Pt II .